POTENSI SUMBERDAYA AIR SEBAGAI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) DALAM MENCAPAI SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI DESA RANTAU KERMAS, KECAMATAN JANGKAT, KABUPATEN MERANGIN, PROVINSI JAMBI - Deliana Siregar, Anggi; Juventa, Juventa; Ritonga, D.M. Magdalena; Rarasati, Niken; Annura Rizky, Shazkya (JOURNAL ONLINE OF PHYSICS, 2023)
Â Â Â Â Â Â Â Â Â Energy resources are resources that can be processed by humans so that they can be used to meet energy needs. Water resources are a renewable natural resource that has a volume with constant conditions in the hydrological cycle. Microhydro Power Plant (PLTMH) is renewable energy that utilizes water resources as an energy producer where the energy produced is classified as small scale energy (less than 200 kW). Electrical energy is energy that is produced from changing other energy that has strength and capacity. Sustainable Development Goals (SDGs) are a new development agreement agreed upon at the UN general assembly in September 2015 with 17 goals to encourage changes towards sustainable development, one of which is regarding clean and affordable energy which is contained in point 7. The location of this research is to determine the potential and estimate the availability of energy to fulfill electricity needs in Rantau Kermas Village,ANGKAt District, Merangin Regency, Jambi Province. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â